Sociocultural Linkages as Causes of Stunting Village in the Community of Tanjung Village, Mempawah Hilir District, Mempawah District - Chainar, Chainar; Thea Purnama, Desca; Elyta, Elyta; Apriyanto, Dhidik; Marini, Marini (International Journal of Multidisciplinary Approach Research and Science, 2023)
Mempawah Regency is a Regency with high cases of stunting, the government's efforts to reduce stunting rates by providing nutritious food assistance to babies at risk of stunting. Stunting is not only a matter of nutrition, but the causes of stunting are complex. This study aims to describe the existence of sociocultural linkages as a cause of stunting. The research method used descriptive qualitative approaches; the informants consisted of 7 people from several government groups, health workers, traditional shops, and communities whose children were stunted; the technique for determining informants used a purposive technique, and the data collection techniques were interviews, observation, and documentation. The results of the study indicate that there is a relationship between low education, many early marriages.